Problematika Penerapan Pidana Di Bawah Minimum Khusus Dalam Perkara Tindak Pidana Narkotika - Muhamad Fuady; Kristiawanto Kristiawanto; Mohamad Ismed (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
Juridically, Law Number 35 of 2009 concerning Narcotics is a legislative product produced in order to provide certainty in law enforcement for narcotics crime. The substance of this law regulates the criminal act of narcotics, which is about prohibited or permissible acts accompanied by criminal threats if the prohibition is violated. However, in the current practice of criminal justice there are problems related to legal certainty for the implementation of the narcotics law, because it turns out that the convictions made by judges against the accused of narcotics crime are not in line with the narcotics law. The imposition of crimes below the special minimum limit by the judge is very contrary to the provisions of Law Number 35 of 2009 concerning Narcotics so that this creates legal uncertainty which has implications for the effectiveness of law enforcement on narcotics crime in Indonesia.Keywords: Special Minimum Crime, Narcotics Crime AbstrakSecara yuridis, Undang-Undang Nomor 35 Tahun 2009 Tentang Narkotika merupakan produk legislatif yang dihasilkan dalam rangka memberikan kepastian dalam penegakan hukum tindak pidana narkotika. Substansi undang-undang tersebut mengatur mengenai tindak pidana narkotika, yakni tentang perbuatan yang dilarang atau dibolehkan yang disertai ancaman pidana apabila larangan tersebut dilanggar. Namun dalam praktik peradilan pidana saat ini terdapat permasalahan terkait dengan kepastian hukum atas pelaksanaan undang-undang narkotika, karena ternyata putusan-putusan pemidanaan yang diputuskan oleh hakim kepada terdakwa tindak pidana narkotika tidak sejalan dengan undang-undang narkotika. Adanya penjatuhan pidana di bawah batas minimum khusus oleh hakim sangat bertentangan dengan ketentuan Undang-Undang Nomor 35 Tahun 2009 tentang Narkotika sehingga hal ini menimbulkan ketidakpastian hukum yang berimplikasi pada efektifitas penegakan hukum tindak pidana narkotika di Indonesia.Kata Kunci: Pidana Minimum Khusus, Tindak Pidana Narkotika